Paraoxonase-2 Silencing Enhances Sensitivity of A375 Melanoma Cells to Treatment with Cisplatin - Roberto Campagna; Tiziana Bacchetti; Eleonora Salvolini; Valentina Pozzi; Elisa Molinelli; Valerio Brisigotti; Davide Sartini; Anna Campanati; Gianna Ferretti; Annamaria Offidani; Monica Emanuelli (MDPI AG, 2020)
Melanoma represents the most aggressive skin cancer, being responsible for the majority of deaths related with these neoplasms. Despite chemotherapy represents a frontline approach for management of the advanced stages of the disease, it displayed poor response rates and short-term efficacy due to melanoma cell resistance. Therefore, the discovery of molecules that can be used for effective targeted therapy of melanoma is crucial. In this study, we evaluated the impact of paraoxonase-2 (PON2) silencing on proliferation, viability, and resistance to treatment of the A375 melanoma cell line with chemotherapeutic drugs dacarbazine (DTIC) and cisplatin (CDDP). Due to the enzymes ability to counteract oxidative stress, we also evaluated the effect of enzyme knockdown on reactive oxygen species (ROS) production in cells treated with CDDP. The data reported clearly demonstrated that PON2 knockdown led to a significant reduction of cell proliferation and viability, as well as to an enhancement of A375 sensitivity to CDDP treatment. Moreover, enzyme downregulation was associated with an increase of ROS production in CDDP-treated cells. Although further analyses will be necessary to understand how PON2 could influence melanoma cell metabolism and phenotype, our results seem to suggest that the enzyme may serve as an interesting molecular target for effective melanoma treatment.